2003
DOI: 10.1093/rheumatology/keg058
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the prostate presenting as polymyalgia rheumatica

Abstract: Carcinoma of the prostate presenting as polymyalgia rheumatica SIR, Polymyalgia rheumatica (PMR) is a relatively common disorder characterized typically by morning stiffness and aching of the shoulder and hip girdles, neck and torso in patients over the age of 50 w1x. Patients often complain of malaise, fatigue, anorexia, weight loss and fever w2x. The diagnostic criteria proposed by Jones and Hazleman in 1981 w3x are somewhat non-specific and are listed below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 5 publications
0
12
0
2
Order By: Relevance
“…There have been reported associations between malignancies (including prostate cancer 5,6 ) and polymyalgia rheumatica. In many cases it has been quoted that symptoms of polymyalgia rheumatica usually resolve following effective tumour control.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reported associations between malignancies (including prostate cancer 5,6 ) and polymyalgia rheumatica. In many cases it has been quoted that symptoms of polymyalgia rheumatica usually resolve following effective tumour control.…”
Section: Discussionmentioning
confidence: 99%
“…Prior cases of metastatic prostate cancer mimicking PMR have been reported [13]. Other malignancies reported to mimic PMR include solid tumors of the kidney, stomach, colon, lungs, pancreas, uterus and ovaries, and hematologic malignancies such as multiple myeloma and lymphoma [4, 5, 14].…”
Section: Discussionmentioning
confidence: 99%
“…Horne et al [6] first reported the co-existence of these two situations. Simultaneous clinical manifestation of temporal arteritis and PMR with other malignant diseases such as squamous cell carcinoma of the tongue [25], myelodysplastic and myeloproliferative syndromes [26], carcinoma of the prostate [27], adenocarcinoma of the lung [28] and renal cell carcinoma [29] have also been reported. In our case, GCA presented with relatively mild local symptoms and also constitutional symptoms.…”
Section: Discussionmentioning
confidence: 99%